An Interleaved Boost Converter Based PFC Control Strategy for BLDC motor - V. Ramesh; Y. Kusuma Latha (Institute of Advanced Engineering and Science, 2015)
In this paper, interleaved power factor correction (PFC) boost converter based control strategy for BLDC motor has been Proposed. The converter exhibits the characteristics of voltage doublers for duty greater than 0.5. The switching losses and losses during reverse recovery operation are considerably reduced in this proposed topology. This is due reduction in switching voltages due to voltage doubler mode. The proposed topology has high efficiency compared to conventional counterpart due to slight increase in conduction losses. In this paper, the proposed PFC control Strategy has been applied to a six switch and four switch VSI fed BLDC Motor drive for effective torque ripple minimization. A comparison is also made between the six switch and Four Switch VSI fed PMBLDC Motor drive.